Research on the interactive relationship between land use management systems and eco-environmental systems in ecologically fragile areas - Wang, Kunpeng; Xi, Yuan; Xu, Zhanjun; Jia, Mingxuan; Wang, Jiakang; Wang, Lu (Journal of environmental management, 2025)
Understanding the interactive relationship between land use management and the eco-environment is essential for ecological conservation and sustainable regional development. However, study on the interactive relationship between land-use management systems (LUMs) and eco-environmental systems (EEs) in ecologically fragile areas is scarce. In this study, the interaction between LUMs and EEs in the research area from 2005 to 2019 was investigated based on the coupling coordination degree model (CCDM), decoupling model (DM), and hotspot analysis using the agricultural and pastoral intertwined zone (APIZ) in northern China as an example. The results show that (1) the urban land use management and eco-environment levels in the research region first increased and then decreased, reaching a maximum in 2015, there were large differences among prefecture-level cities. (2) The degree of coordination in the study area showed an overall upward trend; the spatial distribution of cities with different degrees of coordination remained stable, and the hierarchical circular system was evident. Over the study period, the coordination level shifted from a mildly imbalanced state to an imminently imbalanced state or a near-coordination state, showing significant spatial correlation characteristics, which were initially enhanced and then weakened, with the maximum value being in 2010. The cold and hot spot zones were relatively stable in terms of spatial distribution. (3) The decoupling states between the two systems were diverse, and the main types of decoupling changed from a strong negative decoupling state to an expansive negative decoupling state, or even a recessive decoupling state. Based on the three-dimensional coupling theoretical framework of “Subject-Medium-Context,” this study reveals the interactive chain of "policy-driven, technology regulation and resource adaptation,” it systematically analyzes the interactive relationship between resource management and environmental benefits in the economic cooperation zones of northern Chinese cities, it provides a new perspective for the sustainable development of ecologically fragile areas. This study provides a relatively strong empirical case for enriching the theory of human ecology while also providing suggestions for promoting healthy and coordinated development between LUMs and EEs. •Explore the interaction between LUMs and EEs using CCDM-DM synthesis methods.•An evaluation system for LUMs was constructed.•The level of LUMs and EEs both increased and then decreased, reaching a maximum in 2015.•The decoupling states between the two systems are diverse.•A reference for other ecologically fragile areas.